Irrigation and fungicide application on disease occurrence and yield of early and late sown sunflower - Maldaner,Ivan C. (2015)
The objective of this study was to evaluate the effect of irrigation and fungicide application on the occurrence of diseases and cypsela yield of two genotypes of sunflower. The experiments were carried out in Santa Maria-RS, during the regular season in 2007 and the late season, in 2008. Plants were sown on 04/09/2007 and 21/01/2008, in a completely randomized design, with four replicates. A 2 x 6 factorial scheme was used, with the sunflower genotypes Aguará 03 and Hélio 358 and six fungicide application schemes, which were determined by the FAST forecasting system, as follows: FAST 16, FAST 22 and FAST 28, without irrigation, FAST 16 IRR under irrigated condition, in addition to irrigated control (CONTROL IRR) and control (CONTROL). Disease progress was analyzed based on weekly observations of the severity of the symptoms. It was verified that irrigation increases sunflower cypsela yield in the regular season, provided that weather conditions are not favorable for the occurrence of alternaria and septoria leaf blights or that fungicides are applied. In the late season, under irrigated condition, fungicide application is necessary to control alternaria and septoria leaf blights.